Confesiones de San Agustin - Zeballos, Eugenio (Libreria Religiosa, Calle de Avino, Num. 20, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬

Confesiones de San Agustin - Zeballos, Eugenio (Libreria Religiosa, Calle de Avino, Num. 20, 1888)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Confessones de San Augustin - Zeballos, Eugenio (Capasulta, Folhas, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Confessones de San Augustin - Zeballos, Eugenio (Capasulta, Folhas, 1888)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage